Multivariable analysis of potential evaporation from moist asphalt mixture. (15th November 2015) - Garcia, Alvaro; Hassn, Abdushaffi; Chiarelli, Andrea; Dawson, Andrew
Highlights: The air voids distribution of asphalt mixture has been characterized. Water evaporation has been correlated to the air voids properties. The main factors affecting water evaporation from asphalt roads have been identified. Abstract: Asphalt pavements are normally dark colored and may get a very high temperature difference with the environment during daytime, but the influence of water evaporation in their temperature is unknown. Water evaporation experiments have been conducted using asphalt mixture with various air voids contents while monitoring the surface temperature and heat flux. It was observed that a relationship exists between the evaporation rate, the heat flux, and the surface temperature during water evaporation. In addition, the evaporation rate has been related to air voids parameters such as air voids content and diameter, tortuosity, or the Euler number.